Current Practices of Animal Farming, Community Habits and Water Scarcity: A Different Approach for the Global Water Issues. Issue 1 (1st September 2015) - Gallardo, Veronica
Abstract : In 2015, the United Nations reported that around 70% of water used by humans was allocated to agriculture, which, due to the extensive and inappropriate practices, constitutes one of the main causes of nature depletion, deforestation, soil erosion, and water pollution. Animal farming is considered to be one of the most demanding industries in terms of land, water, supplementary food, and other resources. Studies have demonstrated that the volume of water necessary to produce vegetables is far less than that required to produce meat. For example, a kilogram of vegetables can be grown with just 2% of the water required for a kilogram of beef, or 7% of that required for a kilogram of chicken (Mekonnen and Hoeskstra 2012 ). Livestock constitutes an environmentally expensive industry. A change in the matrix of production would be driven by the consumer's preference to consume plant‐based food products over animal‐based food products. This would alleviate the pressure exerted by human activity on land and aquatic ecosystems. Consumers' food preferences are subject to a large number of variables, including historical, social, and educational influences. The consumption of plant‐based food is associated with weakness, poverty (largely in developing countries), lack of taste, disease, or even luxury (mainly in developed countries). Consequently, there is a tendency to reject the idea of adopting plant‐based diets. In this study, it was found that it is possible to implement substantial change in the current models of food production, which are focused on animal farming practices, to tackle world's water issues by supporting behavioural change processes that influence food choices in consumers in favour of more sustainable ones. In addition, it was found that despite the cultural challenges, it is possible to stimulate a transformation of the production lines. In doing so, this transformation would support economic development and cultural plasticity.